Land has memory: how we use history to reveal memory - Cole, Madelyn Grace (Kansas State University, 2021)
We seem to lack a deep understanding of our cultural and natural history. Without a knowledge of our history, and if we do not know our history, we cannot fully understand ourselves or our common humanity. We must gain a deeper understanding of our cultural and natural history. With more in-depth knowledge, we can become better stewards of the land and better face climate change impacts to prepare for a better tomorrow. This project report is compiled from an initial background research of sense of place, place attachment, benefits of trail design, and cultural and ecological memory, leading into an analysis of five different case studies. From the case studies “Best Design Practices” were developed and then applied into the final product of this report: a design application of a “Trail of Stories.” Stories are a direct product of an individual’s memory or a collective memory. This “Trail of Stories” is presented through the histories of four different places (Lenexa, De Soto, Eudora, and Lawrence, KS) along a 36- mile trail corridor along the K-10 highway of Eastern Kansas and showcases the historical aspects of these four cities. From the historical aspects, cultural and ecological memories emerged to create stories along the trail corridor. The master plan for the contiguous trail, the four designed nodes in each city along the trail, and the overall design application were informed from a literature study, case studies, and qualitative assessments. By knowing our combined cultural and natural history, the land may reveal wisdom and memory for a healthier future landscape. By becoming better stewards, advocates, nurturers, and protectors, the land gains significant support and hope for a better future. Our past teaches us, informs us, and compels us to try harder, do better, and strive for a more resilient future. Through memory, we can deepen our connection with the land and our understanding of the land for a better tomorrow for us all.
Keywords: History; Memory; Landscape; Sense of place; Stories; Trail design